Etiological and pathogenetic aspects of non-specific bacterial vaginosis - Ananieva, M. M. (Zaporozhye Medical Journal, 2018)
The aim of this review was the biological properties analysis of microorganisms known as the main contributors to the non-specific bacterial vaginosis development. The mechanisms of anaerobic vaginal microflora pathogenic action have been found out to be the main cause of non-specific inflammatory processes. Special attention was given to the genera of Mobilunkus spp., Atopobium spp., Prevotella sp. representatives, which were studied as vaginal flora due to the modern diagnostic methods and techniques development. The homeostasis of the vaginal ecosystem results from complex interactions and synergies among the host and different microorganisms that colonize the vaginal mucosa and healthy vaginal microbiota is generally dominated by Lactobacillus spp. Lactobacilli which have been known to be antagonistic toward a variety of microorganisms. In cases of bacterial vaginoses, the proportion of Lactobacilus spp sharply decreases, while the share of anaerobic microorganisms increases: Gardnerella vaginalis,Atopobium sp., Mobiluncus sp., Prevotella sp. The virulence factors of Gardnerella vaginalis pathogenicity are: its ability to form biofilms; the presence of genes responsible for cytotoxicity. The ability of Gardnerella vaginalis, Atopobium sp., Mobiluncus sp., Prevotella sp. to produce short chain volatile fatty acids isomers results in the vaginal mucosa irritation (itching or burning) and discharge with unpleasant odour in BV associated with these microorganisms. Atopobium vaginae, together with Mobiluncus spp. and Prevotella spp., provoke the accumulation of pro-inflammatory cytokines. The whole mechanism leads to an inflammation worsening in BV and stimulates the chronic process development. Both microorganisms Mobiluncus spp. and A. vaginae are competitive lactobacilli in relation to the glycogen consumption. Conclusions. Analysis of literature shows that pathogens of non-specific bacterial vaginosis have wide range of pathogenicity factors. This provides pathogenesis and clinical signs of the disease.